The effect of the situation on leaving out the forgotten non-metaphorical object in the Holy Qur’an - Taher Ayez, Yassin ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This research presents a vision for reading the text in application to the idea of the situation, in which it examines the effect of the conditions that shaped the situation, which called for the transitive verb to be placed in the position of the intransitive verb by forgetting its object, in situations that required that, which are the situations of: (separation; sanctification; information; praise; warning; discipline; glorification; alleviation; complaint). The researcher relied on the attachment to the aspects of rhetorical effect in the system, which helped the linguistic structure respond to the occasions of the situation, as it moves in accordance with the purposes and objectives. He also relied on the flexibility of the linguistic system in keeping pace with the semantic transformations that occur due to the influence of the situation, including the shifts that justified the departure from mentioning the object, and corrected its omission and forgetting. He devoted the research to the forgotten non-metaphorical, and investigated its omission in a selection of noble Qur’anic texts, to demonstrate the attachment of this forgetting to the situation